Neurocutaneous Melanomatosis with a Rapidly Deteriorating Course - Chu, Winnie C.W.; Lee, Vincent; Chan, Yu-leung; Shing, Matthew MK; Chik, Ki-wai; Li, Chi-kong; Ma, Kwok-chiu (American Journal of Neuroradiology, 2003)
Summary: Neurocutaneous melanosis is a rare congenital syndrome characterized by large or multiple congenital melanocytic nevi and benign or malignant pigment cell tumors of the leptomeninges. The prognosis is extremely poor for symptomatic patients, even in the absence of malignant melanoma. We present serial MR imaging findings in the brain and spine of a child with congenital giant hairy nevi who developed progressive leptomeningeal melanomatosis and whose neurologic condition rapidly deteriorated.